Exploring repositioning movements in sitting with 'at risk' groups using accelerometry and interface pressure mapping technologies. Issue 1 (February 2018) - Stinson, May; Ferguson, Rachel; Porter-Armstrong, Alison
Abstract: Background: Despite high quality guidelines underpinning pressure ulcer care (NPUAP/EPUAP/PPPIA, 2014), pressure ulceration still poses a significant financial impact on health care services in treatment and staff costs as well as having a profound effect on the health and quality of life of individuals experiencing them. Repositioning is a key preventative technique recommended by occupational therapists and other health care professionals. The frequency and quality of repositioning movements performed by individuals, however, can be difficult to determine. This paper explores the use of technology in monitoring repositioning movements in sitting. Objective: To explore the outputs of technologies such as interface pressure mapping systems and accelerometers in enabling the therapist to accurately monitor seated behaviour and enhance practice through targeted interventions to prevent sitting acquired pressure ulceration. Method: Reviewing the findings of two recent research studies with 'at risk' cohorts (spinal cord injury; elderly orthopaedic), using accelerometry and seated interface pressures, this paper will highlight how useful this technology is in clinical practice to monitor weight shifts and repositioning behaviours. Result: Both studies illustrated that the majority of individuals did not adhere to the frequency or magnitude of movements currently recommended to redistribute seating interface pressures. When repositioning was performed it was ineffective in reducing seated pressures. Conclusion: In an era of personalised medicine, technology has an important role to play in providing the service user, caregivers and healthcare staff with important biofeedback information about seated behaviours, particularly those that minimise the risk of developing sitting acquired pressure ulcers. This information can augment occupational therapists' clinical decision-making in maximising active pressure ulcer prevention. Highlights: Most individuals with spinal cord injury performed insufficient weight shifts. Technology showed most weight shifts are ineffective in ischial pressure reduction. Elderly orthopaedic patients are at risk of sitting acquired pressure ulcers. Technology could be used clinically to monitor weight shifts and repositioning.